Tirso de Molina and The Trickster of Seville: The Traditionalist Hypothesis and the State of the Question (Castilla. Estudios de Literatura, 2011)
This paper analizes the critical and methodological basis of the two recent Studies about the problems on textual priority and authorship between Tan largo me lo fiáis and El burlador de Sevilla: the edition according to William F. Hunter’s text and the book by Laura Dolfi on the relationship between Tirso de Molina and Don Juan. Our study remarks important omissions in both works, both in the bibliographical field and the ecdotical basis regarding the two texts. We claim that both authors, supporters of the traditional hypothesis on authorship and priority, support their points of view in the form of critical opinions formulated in an insufficient way from the critic point of view and in an incomplete and biased way regarding ecdotical possibilities of both texts.